A modified local approach including plastic strain effects to predict cleavage fracture toughness from subsize precracked Charpy specimens. (February 2020) - Ruggieri, Claudio
Highlights: Extension and application of a modified Weibull stress incorporating plastic strain effects. Fracture toughness values for an RPV steel depend strongly on specimen geometry. Marked differences in crack front stresses between subsize PCVN and large C(T) specimens. The modified Weibull stress model effectively removes specimen geometry effects on cleavage fracture toughness. The standard Beremin model provides much conservative predictions of cleavage fracture toughness. Abstract: This work addresses a probabilistic, micromechanics-based methodology incorporating plastic strain effects on cleavage fracture and its dependence on the microcrack distribution. The present model extends current developments of a local approach to fracture (LAF) adopting a plastic-strain based form of the Weibull stress ( σ ̃ w ) to assess changes in cleavage fracture toughness for a reactor pressure vessel (RPV) steel due to constraint loss effects in subsize precracked Charpy (PCVN) specimens. Cleavage fracture toughness data obtained by Rathbun et al. (2006) for an A533 Gr B reactor pressure vessel steel are employed to demonstrate the capability of the modified LAF in predicting the strong influence of specimen geometry on fracture toughness. By combining detailed non-linear, 3-D finite element analyses for the side-grooved C(T) and PCVN specimens with varying geometries, the plastic-strain based form of the Weibull stress is shown to effectively remove the dependence of J c -values on specimen geometry thereby generating more accurate assessments of cleavage fracture behavior in larger crack configurations from small specimens.